2014
DOI: 10.1111/ppl.12222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shoot removal on remobilization of carbon and nitrogen during regrowth of nitrogen‐fixing alfalfa

Abstract: The contribution of carbon and nitrogen reserves to regrowth following shoot removal and the processes involved in the reduction of nodule functioning were studied in alfalfa plants (Medicago sativa L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 52 publications
2
27
0
2
Order By: Relevance
“…Under water restriction, these changes in the level of endogenous phytohormones induce changes in gene expression that affect the synthesis, production and accumulation of several metabolites as part of an osmoregulatory response, such as carbohydrates, amino acids and organic acids, in different plant organs [25]. Several studies have clearly demonstrated that N and C metabolism plays a very important role in the water stress response [12,26,27]. It has been suggested that some amino acids can be transported from shoots to nodules as systemic signals for BNF under drought conditions [8,28] and that amino acids can represent an alternative source of C and energy for the bacteroid [29].…”
Section: Introductionmentioning
confidence: 99%
“…Under water restriction, these changes in the level of endogenous phytohormones induce changes in gene expression that affect the synthesis, production and accumulation of several metabolites as part of an osmoregulatory response, such as carbohydrates, amino acids and organic acids, in different plant organs [25]. Several studies have clearly demonstrated that N and C metabolism plays a very important role in the water stress response [12,26,27]. It has been suggested that some amino acids can be transported from shoots to nodules as systemic signals for BNF under drought conditions [8,28] and that amino acids can represent an alternative source of C and energy for the bacteroid [29].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the difference in root mass between invasive and native J. vulgaris was solely due to the differences in root carbohydrate storage of which invasive genotypes had allocated less to the roots. Since root carbohydrate storage has been positively associated with plant regrowth after defoliation (Donaghy and Fulkerson, 1997; Aranjuelo et al, 2015), invasive J. vulgaris is supposed to have poorer regrowth ability. This is consistent with the findings that native J. vulgaris genotypes showed better regrowth after complete defoliation by clipping in a competition-free condition in a common garden experiment (Joshi and Vrieling, 2005; Lin et al, 2018) and after herbivory by the generalist Mamestra brassicae or the specialist T. jacobaeae under intraspecific competition (Lin et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Alfalfa is also an important cultivated forage legume in many countries around the world. However, soil salinity and alkalinity severely affect formation of nodules and symbiotic nitrogen‐fixation capacity, and thereby restrict alfalfa yield (Aranjuelo et al ). Therefore, improving the salt–alkaline tolerance of alfalfa through transgenic molecular breeding technology will largely expand its planting area.…”
Section: Introductionmentioning
confidence: 99%